Photic Retinopathy: Diagnosis and Management of This Phototoxic Maculopathy - Mihaela Madalina Timofte Zorila; Livio Vitiello; Filippo Lixi; Alessia Coppola; Feyza Cukurova; Alfonso Pellegrino; Giuseppe Giannaccare (Life)
Photic retinopathy is an uncommon clinical entity characterized by retinal damage brought on by excessive exposure to light without protection. It encompasses several distinct clinical categories, including solar maculopathy, handheld laser maculopathy, arc welding maculopathy, and iatrogenic macular degeneration. These clinical entities result from exposure to diverse light sources, such as solar radiation, laser pointers, welding arcs, and operating microscopes during ophthalmic procedures. Patients typically present with bilateral but asymmetric symptoms, including reduced visual acuity, central or paracentral scotomas, photophobia, metamorphopsia, and headaches. After exposure, most people can recover on their own in a matter of weeks to six months without the need for special care. However, thanks to their anti-inflammatory properties, several clinical cases reporting the use of steroids for acute photic retinopathy have been documented in the scientific literature, together with the use of antioxidants. The purpose of this review is to provide an update on this phototoxic maculopathy, describing its different clinical entities, diagnosis, and treatment options, and also focusing on the role of optical coherence tomography for its management.